The Development of Human Capital and the Economic Growth - Hovsepyan, Volodya (Bulletin of Yerevan University G: Economics, 2015)
Economic growth is a necessary and decisive condition for raising the standard of living of the population. Expansion /development / of human needs and their quality potential constantly faced with the boundary of economic opportunities. In this regard, an important role is given to softening and flattening of these limitations, associated with the development of human capital. From this perspective, the article analyzes the problems of the development of human capital.
Keywords: economic growth, human capital, needs, standard of living, transformation, national income, gross domestic product